2016
DOI: 10.1080/21645515.2016.1171430
|View full text |Cite
|
Sign up to set email alerts
|

MYCN-targeting vaccines and immunotherapeutics

Abstract: Amplification and concomitant overexpression of the MYCN oncogene is a frequent event in many malignancies including the childhood tumors, neuroblastoma and medulloblastoma. MYCN is only expressed in a defined time frame during early developmental processes, 1 which is beneficial for approaches combatting tumor-specific MYCN. However, MYCN is a transcription factors that was considered a poor drug target, until recent approaches suggested that down-regulation of MYCN could be possible by indirect targeting usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Early studies have shown that most MB tumors have only nominal immune-cell infiltration and tumor cells have absent or deficient antigen-presenting machinery [62,63]. Despite the apparent lack of tumor surveillance, there is growing evidence that checkpoint inhibition, immunization, or viral therapy may be of benefit [64,65,66].…”
Section: Medulloblastomamentioning
confidence: 99%
“…Early studies have shown that most MB tumors have only nominal immune-cell infiltration and tumor cells have absent or deficient antigen-presenting machinery [62,63]. Despite the apparent lack of tumor surveillance, there is growing evidence that checkpoint inhibition, immunization, or viral therapy may be of benefit [64,65,66].…”
Section: Medulloblastomamentioning
confidence: 99%
“…MYCN belongs to the MYC family of proto-oncogenes and transcription factors, encoding a helix-loop-helix (bHLH) domain-based protein, implicated in the progression of the cell cycle through the G1/S transition. MYCN represents a critical oncogene, maintaining the tumorigenic state in several cancer types, implicated in cancer initiation, progression and invasion [ 141 , 191 , 192 ]. C-Myc downregulation at 72 h in the presence of CRCs and DMCRT for A172 cells and in the presence of DMCRT for TE671 cells could represent another mode of saffron cytotoxicity and induction of apoptosis in a MYCN-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…However, the compounds that can interfere with MYCN interaction with its partner MAX as a way to block its transcriptional action, were not efficient in vivo [57], dampening their development in clinical testing. Strategies to exploit MYCN as a tumor-associated antigen for immunotherapy deserve further functional validation [58]. The ALK gene is altered by gain-of-function point mutations in around 14% of high-risk NB and represents an ideal therapeutic target given its low or absent expression in healthy tissue postnatally [59].…”
Section: Molecular Mechanisms and Therapeutic Targets In Neuroblastomamentioning
confidence: 99%